RS-485 interface for Boiler Header Inspection Robot prototype - Basri N.M.H.; Sahari K.S.M.; Mohideen S.S.K.; Baharuddin M.Z.; Anuar A. (Elsevier Ltd, 2023)
This paper discusses the design of an RS-485 interface for Boiler Header Inspection Robot (BHIR) prototype. BHIR is a robot developed for inspection of boiler headers in thermal power plants which are enclosed pipes and can range from 3 to 20 meters in length. They are horizontal in configuration and have boiler tubes inlets and outlets. The current prototype is tether based and requires cables up to 20 meters. RS-485 interface is presented in this paper which is used to develop a communication link between PC-based control (GUI interface) with the BHIR Prototype on-board controller. Since RS-485 is reliable and stable in monitoring and controlling system, BHIR Prototype can work effectively throughout the length of the boiler header. 2012 The Authors.